The Life and Afterlife of a Socialist Media Friend - Bloch, Kinga (VIEW Journal of European Television History and Culture, 2013)
This paper analyses how the relationship of the Polish audience to a series from the 1970s, Czterdziestolatek (The Fourty-Year Old) evolved during socialism and after the Fall of the Iron Curtain. Contemporary reactions to the original series and a new season that was produced in the early 1990s are compared to nostalgic recollections and memories of the programme in later periods. The study discusses how the Polish audience uses the programme as a historical document today and whether there is a generational difference in the perception of the audiovisual interpretation of Polish everyday life in the 1970s.